2022
DOI: 10.3390/en15020618
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Status of Research and Innovation Actions on Electrofuels under Horizon 2020

Abstract: Europe stated the ambitious target of becoming carbon neutral by 2050 to combat climate change and meet the requirements imposed by the Paris Agreement, and renewable energy has proved to be a promising solution for the decarbonization of many sectors. Nonetheless, their aleatory nature leads to grid unbalances due to the difference between supply and demand. Storage solutions are needed, and electrofuels become a key factor in this context: they are fuels produced from electricity, which leads to carbon-neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Brynolf et al [5] focusing on production costs; and more recently Ababneh and Hameed [28] reviewing the production processes, costs and environmental impacts; and Ince et al [29] presenting 79 system-level mathematical modeling and simulation studies of different e-fuel production pathways (including no differentiation in relation to transport mode). Marzi et al [30] analyzed the state-of-the-art of e-fuels research by specifically mapping projects on e-fuels production funded by the EU Horizon 2020 Programme and found the largest interest to be in hydrogen. Sherwin [31] conducted and optimized a techno-economic assessment focusing on how e-fuel cost could be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…Brynolf et al [5] focusing on production costs; and more recently Ababneh and Hameed [28] reviewing the production processes, costs and environmental impacts; and Ince et al [29] presenting 79 system-level mathematical modeling and simulation studies of different e-fuel production pathways (including no differentiation in relation to transport mode). Marzi et al [30] analyzed the state-of-the-art of e-fuels research by specifically mapping projects on e-fuels production funded by the EU Horizon 2020 Programme and found the largest interest to be in hydrogen. Sherwin [31] conducted and optimized a techno-economic assessment focusing on how e-fuel cost could be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…Several projects were analyzed by Marzi et al (2022) where the authors found 70 projects about electro-fuels by using the CORDIS portal. The scholars distinguished the main research areas in electrofuel development as well as identified the key features, project aims, integration levels, and the outcomes of the projects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, researchers discovered the field of electro-fuel production of the projects funded in the Horizon 2020 program. The projects were selected based on specific features under the "Secure, Clean and Efficient Energy" challenge [5]. In another paper, research projects on smart distributed energy systems were collected in the energy sector based on predefined keywords [6].…”
Section: Introductionmentioning
confidence: 99%